Anna Hood: capstone - Hood, Anna, artist (Colorado State University. Libraries, 2023)
The artist's statement: When beginning my designs, I ask myself what story or idea am I trying to share with others. I take a concept and try to look at it from every angle. At the start, the important part is not the one idea I chose to elaborate more on. It's all the research that got me there and helped me better understand my project's goals. My work is like starting and finishing a puzzle. I start by choosing the puzzle, then study the goal and work hard until it all fits together. By testing a variety of different layouts and styles, eventually finding the perfect fit for my project's tone. I take my inspiration from my surroundings and everyday life. Whether it's emotions, looking at solutions to problems, or designs in nature, they all help me develop unique concepts for projects. I believe my style is minimalist, I take a simple approach that will appeal to all crowds. My goal for my projects is creating a way to share ideas and information in a way that will last in others mind.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design